Evaluation of The Performance of Incubation Business Services in Morocco - Kenza Bouarara; Mohamed Oudgou; Abdelilah Baguare (Research Synergy Foundation, 2023)
The purpose of this article is to make an empirical assessment of the services offered by the incubation structures in Morocco. To do this, we will focus on the identification of the incubation actors and the services offered by these structures. Within this framework, two studies are envisaged: the first one aims at exploring entrepreneurial incubation as it is conceived and seen by its practitioners, and a confirmatory method that will focus on the perception of this practice on the part of